Inclusive education in Greece - Kaltsouni , Paraskevi (Social work and education, 2021)
The educational system in Greece, in terms of inclusive education, has changed a lot the last decades in Greece, while disabled students had to follow all these reforms in educational and social context. In other words, along with the steps of other countries, Greece has been making attempts to adopt an institutional framework for integration, through a holistic approach that will provide sustainable social and educational environments to all children with disabilities. Therefore, the aim of this study is to describe the forms, models and practices of integration during the last decades in Greece.